Integrated and participatory municipal tourism management model, for the strengthening of cultural tourism offer - Cayotopa Ylatoma, Cilenny (2018)
The present investigation pursues the purpose of evaluating the tourist management and proposing an integrated and participative municipal tourism management model to strengthen the design of the cultural tourist offer, in the district of Zaña, Chiclayo - Peru, for this purpose a plan of action of management of the tourist offer, to improve the promotion of the tourist offer in this district. In that sense, tests were applied, surveys to the social actors of the community and the questions included were the result of identifying the most outstanding problems of the municipal tourist management, in the same way it is recorded the tourist resources and tourist services with which it has the district of Zaña. The obtained from the investigation showed that the tourist management in the district of Zaña, present deficiencies and needs to improve this process, taking into account the resources and tourist services, which constitute the potentialities of the district. Based on the diagnosis made, the proposal for an integrated and participatory municipal management model was constructed, which will allow the protagonism of social actors, as well as the valuation of tourism resources and services, to strengthen the design of cultural tourism in this area. District, led by the municipality and with the participation of businessmen and the community in general, understanding that of the tourism development, the progress of this town also depends.